Comparative Perspectives on Afro-Latin America - Burdick, John, 1959-; Dixon, Kwame (Book collections on Project MUSE., 2012)
This original collection of essays discusses the experience of blackness and cultural difference, black political mobilization, and state responses to Afro-Latin activism throughout Latin America.